KENDALA-KENDALA YANG DIHADAPI GURU HONOR DALAM PROSES PENGAJARAN PADA SMP NEGERI 8 BANDA ACEH - Fitriana, Zakaria, Irma Anggraini (Jurnal Economica Didactica, 2019)
ABSTRACTThis thesis is entitled "The Obstacles Faced By Honorer Teachers In Teaching Process At Junior High School 8 Banda Aceh". The purpose of this study is to find out the obstacles faced by honor teachers in the teaching process at Banda Aceh State Middle School 8. This study uses a qualitative approach with a type of descriptive research. The data of this research is derived from the teacher's utterances regarding the obstacles faced in the teaching process, while the data source is the honorarium teacher at Banda Aceh Junior High School 8. Data collection is done by: (1) library research (2) field research conducted by observation, interviews, and documentation. The results of this study indicate that there are various variations of constraints experienced by honor teachers in Banda Aceh Junior High School, namely: internal constraints mastery of material that is not in the field of science, constraints in using learning methods, constraints in the time set, constraints in overcoming students who have different behaviors, constraints in overcoming students who have different backgrounds, constraints in lack of interest and student motivation in learning, constraints with inadequate facilities due to limited facilities owned by the school, constraints in obtaining learning media, constraints faced by honorarium teachers in terms of classroom management, constraints in communicating with students and constraints in communicating with parents of students.Keywords: the obstacles, honorer teachers